The Role of Social Support in Preventing Self-Harm Behavior in Depressed Adolescents - Rif'ah, Erwin Nur; Arridlo, Alfia Qumara (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Adolescents aged 20-24 must have maturity in thinking and acting to be vulnerable to psychological problems. If adolescents cannot control this condition, it results in depression, which tends to commit self-harm. Efforts to prevent self-harm cannot be separated from the support of other individuals so that the perpetrator is consistent in avoiding it so that he does not commit self-harm repeatedly. Social support significantly increases adolescents' positive attitudes and reduces their psychological burden. This study aimed to analyze the role of social support in preventing self-harm behavior in depressed adolescents. This type of research is qualitative research with a phenomenological approach. The research informants came from Jember Regency, Ponorogo Regency, and the City of Surabaya, namely five depressed teenagers who had repeated self-harm behaviors—data collection techniques using in-depth interviews. This study found that the main informant did self-harm to divert psychological pain into physical pain. Types of self-harm include pulling hair, slashing hands with a razor or knife, banging your head against a wall, and consuming drugs excessively. This study's results suggested that adolescents be more courageous in facing problems, seek mental health assistance from psychologists or psychiatrists, and build emotional closeness with their parents, peers, and the surrounding environment. Keywords: Depression, self-harm, sosial support